Penanaman Pendidikan Karakter Pada Generasi Muda di Dunia Pendidikan Melalui Kegiatan Organisasi Intra Sekolah - Emilda, Andri; Khairiah, Khairiah; Asiyah, Asiyah (Yayasan Darussalam Bengkulu, 2021)
The company is a development organization for young people. An organization can teach you a lot of things, particularly things that aren't connected to academics. Each of the organization's members has a significant effect. Character education, which teaches the younger generation to be responsible, disciplined, and innovative, may take place in a variety of settings. Many young people nowadays, however, do not want to join organisations, either within or outside of their educational institutions. As a result of their own lack of accountability and discipline. Furthermore, they do not wish to expand their creative abilities. This research aims to discover why the younger generation is less interested in entering organizations, as well as to find solutions that will enable the younger generation to exercise responsibility, discipline, and innovation. The qualitative analysis approach was used. The findings revealed that the organization was effective in developing a young generation that was responsible, disciplined, and innovative